Programmable Functionalization of Surfactant‐Stabilized Microfluidic Droplets via DNA‐Tags. (8th April 2019) - Jahnke, Kevin; Weiss, Marian; Frey, Christoph; Antona, Silvia; Janiesch, Jan‐Willi; Platzman, Ilia; Göpfrich, Kerstin; Spatz, Joachim P.
Abstract: Droplet‐based microfluidics has emerged as a powerful tool in synthetic biology. For many applications, chemical functionalization of the droplets is a key process. Therefore, a straightforward and broadly applicable approach is developed to functionalize the inner periphery of microfluidic droplets with diverse reactive groups and components. Instead of covalent modification of the droplet‐stabilizing surfactants, this method relies on cholesterol‐tagged DNA that self‐assembles at the droplet periphery. The cholesterol‐tagged DNA serves as an attachment handle for the recruitment of complementary DNA. The complementary DNA can carry diverse functional groups. We exemplify our method by demonstrating the attachment of amine groups, DNA nanostructures, microspheres, a minimal actin cortex, and leukemia cells to the droplet periphery. It is further shown that the DNA‐mediated attachment to the droplet periphery is temperature‐responsive and reversible. It is envisioned that droplet functionalization via DNA handles will help to tailor droplet interfaces for diverse applications—featuring programmable assembly, unique addressability, and stimuli‐responsiveness. Abstract : Chemical functionalization of microfluidic water‐in‐oil droplets is achieved via hydrophobic interactions of cholesterol‐tagged DNA with the droplet‐stabilizing surfactants. The DNA handle at the droplet periphery serves as a programmable binding site, which can carry an arbitrary group or compound. This method for reversible droplet functionalization is exemplified by attaching functional groups, beads, proteins, and cells to the droplet periphery.